Targeting sterol-O-acyltransferase 1 to disrupt cholesterol metabolism for cancer therapy - Tu, Teng; Zhang, Hongying; Xu, Huanji (Frontiers in Oncology, 2023)
Cholesterol esterification is often dysregulated in cancer. Sterol O-acyl-transferase 1 (SOAT1) plays an important role in maintaining cellular cholesterol homeostasis by catalyzing the formation of cholesterol esters from cholesterol and long-chain fatty acids in cells. Many studies have implicated that SOAT1 plays a vital role in cancer initiation and progression and is an attractive target for novel anticancer therapy. In this review, we provide an overview of the mechanism and regulation of SOAT1 in cancer and summarize the updates of anticancer therapy targeting SOAT1.